La Motivacion Y Su Influencia En El Rendimiento Academico En Los Alumnos Del Decimo Año De Educación Básica Del Colegio Particular Padre Marcos Benetazzo # 1” - Ayala Castillo, Alba (2015)
There are several forms of discipline but usually discipline is a human behavior, which is a behavior as a certain freedom which is governed by certain laws or rules in a way. " In a school discipline it can be expressed as a behavior in which the student is subject to the laws of respect for the teacher and classmates and the classroom. " Considering the stated above discipline in the course is the way in which the student somehow "delivery" respect for the teacher and peers, although the case is given to the teacher and that discipline makes the course whole and therefore we have to indiscipline is the lack of discipline which takes the violation of the golden rule is to respect and care educator at the institution. The discipline is given by different factors such as the environment and the pressure on the educated and that is how the discipline and indiscipline are the exclusive properties of educated and that is supposed to discipline and indiscipline is a fact that "favors "educator. A person may lack discipline when it is under some form of debauchery; take into account that one's freedom ends where the other begins, and that is why both the educator and the educated respect they deserve and that is why there are sometimes undisciplined because sometimes stifles freedom educator or learner there are cases in which the student abuses his freedom causing a violation of freedom of the educator. This research is sopbre school indiscipline in a rural school, critical study that will serve as a model for solving similar problems in other academic units